Qubit Model for Solving the Coverage Problem - Hahanov, V. I.; Litvinova, E. I.; Chumachenko, S. V.; Baghdadi, Ammar Awni Abbas; Eshetie, Abebech Mandefro (EWDTS, 2012)
Qubit (quantum) structures of data and computational processes for significantly improving performance when solving problems of discrete optimization and fault-tolerant design are proposed. We describe a hardware-focused models for parallel (one cycle) calculating the power set (the set of all subsets) on the universe of n primitives for solving coverage problems, minimization of Boolean functions, data compression, analysis and synthesis of digital systems through the implementation of the processor structure in the form of the Hasse diagram. A prototype of quantum device, implemented by programmable logic, is described. A quantum computer is designed for fault-tolerant design and solving optimization problems by way of the brute-force method through the use of set theory. Considering the discreteness and multiple-valuedness of the alphabets for description of information processes, the parallelism, inherent in the quantum computing, is particularly actual when developing effective and intelligent engines for data retrieval in cyberspace or Internet, tools for synthesis of faulttolerant digital primitives and systems, designing and testing digital systems-on-chips, tools for solving problems of discrete optimization. It does not cover the physical basis of quantum computing, originally planted in the works of scientists, focused on the use of non-deterministic quantum interactions within the atom.
Keywords: quantum computer; Qubit; Coverage Problem